A statistical analysis on Renaissance Plastic Industry - Navarro, Jason Ryan M. (College of Engineering, 2001)
The subject of this experiment is a plastic manufacturing company, Renaissance Plastic Industry. The experiment focused on the production of wafer jars. After analyzing the company's problems, through the use of a Streamline Diagnosis Diagram and Ishikawa Diagram, the proponents focused on the problem of too many defective outputs. Defects in the bodies of the products can be classified into three : the occurence of black spots, jagged circumference and unmet weight specifications. Possible factors affecting the incidence of unmet weight specifications were tested through the use of the two factor factorial design and the Analysis of Variance (ANOVA) table. It was concluded that the temperature and the percentage of recycled materials were significant in the incidence of unmet weight specifications. Through hypothesis testing, the set tolerance for the temperature was tested to prove if it was appropriate for the production process of the company. It was concluded that the tolerance set was of the right level. The one factor design, with the aid of the ANOVA table, was used in testing the possible factors affecting the occurence of black spots and serrated circumference. It was determined that the percentage of recycle raw materials and the amount of air pressure present are significant in the occurence of black spots and jagged circumference respectively. The significant levels of each of the factors were determined using the Duncan's Multiple Range Test (DMRT). It was determined that all the levels have significant differences for both the air pressure and the percentage of recycled raw materials used. The results of the statistical analysis were interpreted in terms of their impact on the production process and recommendations were as follows : 1. The percentage of the recycled raw materials used to be decreased to ensure that the output will meet the weight specifications (set 115-118 grams). 2. The temperature and air pressure must be checked regularly in order to make sure that they fall under the tolerance set (172-175 degree celcius and 45-60 kg per cm)